Irritancy ranking of anionic detergents using one-time occlusive, repeated occlusive and repeated open tests - Tupker, R. A.; Bunte, E. E.; Fidler, V.; Wlechers, J. W.; Coenraads, P. J. (Contact dermatitis, 1999)
Discrepancies between the one‐time patch test and the wash test regarding the ranking of irritancy of detergents have been found in the literature. The aim of the present study was to investigate the concordance of irritancy rank order of 4 anionic detergents tested by 3 different exposure methods, namely one‐time occlusive, repeated short‐time occlusive and repeated short‐time open tests. These detergents were sodium cocoyl isethionate (ISE), sodium lauryl sulfate (SLS), soap and disodium lauryl 3‐ethoxysulfosuccinate (SUC). The reactions were evaluated by visual scoring and by transepidermal water loss (TEWL) measurement. When scored visually, the rank order in the one‐time test was: SOAP≥SLS≥ISE>SUC. The other test methods yielded a different order: SLS>ISE≥SOAP>SUC. A similar rank order was obtained with TEWL measurement for all exposure methods. Generally, the concordance among the different exposure methods was high when evaluated by TEWL. The concordance was lower when evaluation was performed by visual scoring. The present study demonstrates that the choice of exposure model and evaluation method may be important variables influencing the outcome of irritancy testing. It is proposed that the repeated open test is the best way to simulate most in‐use situations where the uncovered skin is exposed to detergents. The repeated occlusive test or the one‐time patch test may be better to simulate situations in which the skin is occluded after irritation by detergents.